Attention Level Determination by Using Fuzzy - Mohd Nasir, Haslinah; Mohamed Aminuddin, Mai mariam; Brahin, Noor Mohd Ariff; Mustaffa, Izadora (International Journal of Integrated Engineering, 2020)
For safe driving, it is always crucial to keep 100% attention on driving without distraction. The road accident may happen with just a blink of eyes. Previous studies have shown that peak decrement of N170 wave relates to degrading of attention. However, to determine the level of attention is challenging due to inter-variability of decrement range between subjects. Hence, in this study, the attention level is investigated by analyzing the peak of N170 decrement versus accident score using fuzzy rule-based to minimize the grey area.  Accordingly, three levels of attention are found, i.e., attentive, begin of inattentive and inattentive. 23.3%% or less decrements of N170 peak is associate to significant attentive. When the decrements reach the 34.3% of N170 peak, the subjects showed the inattentive behavior and most of the subjects have shown that, 41.03% of N170 peak decrements is significant inattentive. This finding gives a promising foundation in developing a hardware for attention alarm system.